Are University Librarians Thoughtful About Knowledge Management? A Case with Private Universities in Bangladesh - Mostofa, Sk Mamun; Tonmoy, Tauhidur Rahman (Universitas Pendidikan Ganesha, 2024)
Librarians contribute significantly to the efficient implementation of KM projects as custodians and disseminators of information within the organization. This research provides an overall picture of KM in private university libraries in Bangladesh. The primary aim of this study is to analyze the present status of KM practices in private university libraries in Bangladesh. Library professionals’ level of understanding of KM as well as the methods of recording knowledge in these libraries is also identified. This is a quantitative study. A structured survey questionnaire was distributed among the 11 private university library professionals of Bangladesh to collect primary data. The overall response rate was 89.1%. The collected data has been analyzed by IBM SPSS Statistics Version 25 Software. The results revealed that there is no formal theoretical as well as practical application of KM in Bangladesh’s private university libraries. The library professionals’ understanding of KM is at a generally satisfactory level. The present study also suggests that the most frequently utilized methods to record tacit and explicit knowledge in these libraries are ‘Social interaction’ and ‘Journals’ respectively.